2007
DOI: 10.3113/fai.2007.0224
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Evaluation of Primary Stiffness of Tibiotalocalcaneal Fusion with Intramedullary Nails

Abstract: The IM nails with compression used for TTCF produced good contact surfaces and primary stiffness. They were significantly superior in these respects to the uncompressed nails and the screw construct. The large contact surfaces and great primary stiffness provided by the IM nails in a bone model may translate into improved union rates in patients who have TTCF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
49
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(50 citation statements)
references
References 24 publications
0
49
0
1
Order By: Relevance
“…The 6 (9%) patients that did not complete follow-up (No. 3,4,6,19,27,58) were not the patients with complications except one (No. 6, minor tibial split, see above).…”
Section: Two-year-follow-upmentioning
confidence: 89%
See 1 more Smart Citation
“…The 6 (9%) patients that did not complete follow-up (No. 3,4,6,19,27,58) were not the patients with complications except one (No. 6, minor tibial split, see above).…”
Section: Two-year-follow-upmentioning
confidence: 89%
“…The first biomechanical studies in the literature investigated first-generation retrograde (femoral) nails without foot and ankle specific locking options [14][15][16][17]. Secondgeneration nails with foot and ankle specific locking options such as anteroposterior locking within the calcaneus and/or optional compression were designed to increase stability [18][19][20]. In 2010, another system with a triple-bend retrograde intramedullary nail (A3, Stryker, Airview Boulevard, MN, USA) was introduced [1].…”
Section: Introductionmentioning
confidence: 99%
“…Intramedullary nailing has demonstrated greater rigidity, final stiffness, less deformity with compression, and higher load-to-failure stressors in biomechanical and cadaveric models. 3,12,[14][15][16] Progress of IMN design to incorporate angle-stable locking screws has also increased biomechanical advantages to earlier nail designs with only static screw design. 15,17 Our study suggests that the biomechanical laboratory results are translated in the clinical setting.…”
Section: Historical Perspectivementioning
confidence: 97%
“…5,24 Compression has been shown to be important not only in stabilizing the arthrodesis sites but also in promoting bone healing and allowing for load sharing between implanted devices and native osseous tissue to prevent fatigue fracture of hardware. 2,40 Although most IM nails are designed to generate arthrodesis site compression at the time of surgery, 35,43 this initial compression can be significantly reduced after surgery because of joint settling and bone resorption. In particular, studies using a synthetic bone model reported that 1 mm of simulated resorption can lead to a 90% or greater reduction in compressive load applied by an IM nail, whereas 1.4 mm of simulated resorption leads to a 98% or greater loss of compression for all IM nails tested.…”
Section: Introductionmentioning
confidence: 99%